Warpage Behavior Of Thin Fcbga Package And Prediction Of Its First Interconnect Snag Solder Joint Shape - Lim, Shaw Fa (2020)
The influence of substrate copper density distribution, substrate bump coplanarity, stiffener attach process, and substrate clamping by magnetic boat during die attach towards Flip Chip Ball Grid Array (FCBGA) assembled package warpage were evaluated. The substrate warpage behavior throughout the package assembly process was characterized using shadow moiré. In this study, it was found that a balanced substrate copper density distribution (50/50 ratio), pre-stiffener substrate before flip chip bump reflow, and substrate clamping during reflow able to reduce flip chip solder bridging fall-out. The decrease in solder bridging <1% was due to the lower substrate warpage seen during die attach. In particular, solder bridging fall-out was well-correlated to die attach area warpage. Substrate with and without clamping during reflow has met the package reliability requirement of temperature cycle 1200 condition G (–40 °C to +125 °C). Simulation works through FEA (ANSYS) on the bare substrate and package warpage was carried out and correlated to experiment data. Various material properties and package designs was evaluated from the correlated FEA model and its respective warpage behavior was understood. With understading of warpage data through FEA, SnAg solder joint shape and its solder bridging can be understood through Surface Evolver. The effect of solder volume, gap height and Under Bump Metalization (UBM) size towards solder joint was evaluated. Higher solder volume and smaller gap height led to higher occurrence of solder bridging. Solder joint formation through solder cap copper pillar onto copper trace was predicted through Surface Evolver. It can be shown that copper pillar solder joint geometry can be successfully simulated and agreed with experiment. The relationship between various solder joint influencing factors such as die bump diameters, copper pad geometry, solder height and solder volume were established. The optimum die bump to copper pad width ratio can be obtained through this simulation work. The information can be used to estimate critical volume of solder needed for new, smaller pitch die bump and copper pad design which help to save cost and time by avoiding a large number of experiments prior to mass production.